The epidemiology and antigenic characterization of influenza viruses isolated in Curitiba, South Brazil - Luine RR Vidal; Marilda M Siqueira; Meri B Nogueira; Sonia M Raboni; Luciane A Pereira; Gislene RA Takahashi; Indianara Rotta; Maria do Carmo Debur; Libera M Dalla-Costa (Memorias do Instituto Oswaldo Cruz, 2008)
Several studies conducted all over the world have reported that the influenza virus is associated with great morbidity and mortality rates. In this study, we analyzed the incidence of the influenza virus between 2000 and 2003 in Curitiba. We studied 1621 samples obtained from outpatients and hospitalized patients of both sexes and all ages. The study was conducted at the local primary care health units (outpatients) and at the tertiary care unit (hospitalized) of the General Hospital of the Federal University in the state of Paraná, Brazil. Nasopharyngeal aspirates and, eventually, bronchoalveolar lavage were assayed for the presence of viral antigens, either by indirect immunofluorescence or cell culture. Of the samples studied, 135 (8.3%) were positive for influenza virus, and of those, 103 (76.3%) were positive for type A and 32 (23.7%) for type B. Additionally, positive samples were analyzed by reverse transcription followed by polymerase chain reaction and subtypes H1 and H3 were identified from this group. A high incidence of positive samples was observed mainly in the months with lower temperatures. Furthermore, outpatients showed a higher incidence of influenza viruses than hospitalized patients.